Monitoraggio della contaminazione da microplastiche in esemplari del verme di fuoco Hermodice carunculata (Annelida) provenienti dalle coste del Mar Ionio - Ferrari, Valentina; Simonini, Roberto; Righi, Sara; Prevedelli, Daniela; Bergami, Elisa (Biologia Marina Mediterranea, 2025)
Microplastics are widespread and persistent pollutants in the marine ecosystem. Because of polymer density or biofouling process, microplastics can accumulate in benthic habitats, which can act as a final sink for microplastic deposition. Thus, benthic invertebrates are particularly vulnerable to microplastic ingestion, raising growing concern on the impacts on macrobenthic communities. Therefore, information on the negative effects of microplastic pollution on marine benthic invertebrates are required. Here we investigate the microplastic content in the polychaete Hermodice carunculata, an opportunistic scavenger and predator. An optimized enzymatic and thermo-oxidative digestion method, followed by acid treatment to remove the worm's chaetae, was applied to isolate microplastics from specimens. Then, the suspected microplastics were quantifyed and characterized trough stereomicroscope and spectroscopical technique. A total of 112 suspected microplastics were found in 95% of animals, showing the potential role of H. carunculata as a target for assessing microplastic pollution in Mediterranean benthic predators.